Impacts of electricity grid tariffs on flexible use of electricity to heat generation. (15th November 2016) - Kirkerud, Jon Gustav; Trømborg, Erik; Bolkesjø, Torjus Folsland
Abstract: District heating plants having both electric boilers and alternative fuel options could hold a key in providing flexibility needed for cost efficient integration of variable renewable power. The electricity grid tariff is an important component of the electricity costs of electric boilers, and these tariffs may promote or hamper flexible use of power-to-heat. In this paper, a mixed integer cost minimization model that schedules the operation of different boilers in a district heating plant is developed and applied to analyze the impact of different tariff structures on flexibility provided by electric boilers. The results confirm that the structure of electric grid tariffs significantly influences the flexibility provided and the annual shares of electric boiler use, caused by differences in grid tariff structures, vary from 2% to 17%. Novel tariff structures with time-varying elements increase utilization electricity in low price periods and improve the profitability of power-to-heat as a flexibility solution. The study clearly demonstrates that system effects should be considered when grid tariffs for flexible electric boilers are designed and that novel tariff designs should be more widely adapted. Highlights: Electricity grid tariff structures greatly influence flexible use of power to heat (P2H). Tariff structures with time-varying elements cause more use of P2H when electricity prices are low. Tariff structures with time-varying elements yield cost savings for district heating plants. In thermal power dominated regions, demand charges greatly discourage flexible use of P2H.